Reading "Hamlet" based on Schmitt: seeing Hamlet as demystified and the jurist as Hamlet - Jocelyn-Holt Correa, Emilia (2020)
How can Hamlet be read based on Schmitt? This article analyzes Carl Schmitt’s Hamlet or Hecuba: The Intrusion of the Time into the Play, with aims at understanding the jurist’s interpretation of Shakespeare’s Hamlet. After explaining the ideas from the essay by Schmitt, this paper proceeds to a critical account on how the German philosopher reads the Shakespearian play. The conclusion is that Schmitt’s analysis highlights the character of Claudius and demystifies that of Hamlet. Thus, it attempts to mystify politics and demystify the law at the same time.